2015
DOI: 10.1038/onc.2015.127
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the intestinal stem cell signature gene SMOC-2 is required for L1-mediated colon cancer progression

Abstract: Overactivation of Wnt-β-catenin signaling, including β-catenin-TCF target gene expression, is a hallmark of colorectal cancer (CRC) development. We identified the immunoglobulin family of cell-adhesion receptors member L1 as a β-catenin-TCF target gene preferentially expressed at the invasive edge of human CRC tissue. L1 can confer enhanced motility and liver metastasis when expressed in CRC cells. This ability of L1-mediated metastasis is exerted by a mechanism involving ezrin and the activation of NF-κB targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
68
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 33 publications
6
68
0
Order By: Relevance
“…Ben-Shmuel et al (2013) found that ezrin can be phosphorylated by L1 through Rho-associated protein kinase in colorectal cancer, and that ezrin might be associated with activation of NF-κΒ pathway, which results in tumor cell motility and an increase in the expression of insulin-like growth factor-binding protein 2. These results were consistent with research by Gavert et al (2010) and Shvab et al (2015).…”
Section: Discussionsupporting
confidence: 83%
“…Ben-Shmuel et al (2013) found that ezrin can be phosphorylated by L1 through Rho-associated protein kinase in colorectal cancer, and that ezrin might be associated with activation of NF-κΒ pathway, which results in tumor cell motility and an increase in the expression of insulin-like growth factor-binding protein 2. These results were consistent with research by Gavert et al (2010) and Shvab et al (2015).…”
Section: Discussionsupporting
confidence: 83%
“…Many of these Arntl2-regulated secreted factors were also more highly expressed in metastasis-derived cells lines than in non-metastatic primary tumor-derived cell lines (Figure 6C). Several of these top secreted factors, including Wnt5a, Il-11, and Cxcl5 have been previously implicated in regulating metastatic ability in lung and other cancer types (Bo et al, 2013; Hanaki et al, 2012; Kang et al, 2013; Weeraratna et al, 2002; Zhou et al, 2014), while others, such as Smoc2, Grem1, and Ltbp2, are relatively poorly characterized in metastasis (Table S2 and Shvab et al, 2015). Arntl2 knock-down did not lead to changes in canonical epithelial genes Cdh1 and Epcam or lung differentiation genes Muc1 and Abca3 consistent with Arntl2 not directly affecting cancer cell differentiation (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Smoc2 is widely expressed during embryonic development, enhances responses to angiogenic growth factors, and mediates cell adhesion(Maier et al, 2008; Rocnik et al, 2006). Smoc2 also marks intestinal stem cells, and its induction in colorectal cancer cells was shown to promote epithelial-mesenchymal transition and confer a stem cell-like phenotype (Shvab et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer, the SMOC-1 gene was found to be hypermethylated56 but otherwise very little is known about the role of SMOC-1 in human disease. There is similarly little known about the role of SMOC-2, although there is evidence that SMOC-2 has mitogenic properties and is an important regulator of proliferation57, and can synergise with VEGF and bFGF-induced angiogenesis in endothelial cells58. Like SPARC, SMOC-2 may therefore regulate growth factor signalling.…”
mentioning
confidence: 99%